Design of New Efficient Stream Key Generator to Protect the Classified Information - Abed, Shahad Sameer; Nasir, Ayad Ghazi (Iraqi Journal of Science, 2024)
In this paper, we will create a new stream key cipher generator (KG) that is based on the LFSR unit and a chaotic map. The created KG can be used for a variety of purposes, including cryptography and steganography. The suggested KG is called Efficient Stream KG, and it demonstrates its efficiency when it passes all of the basic efficiency criteria tests, namely the periodicity, linear complexity, correlation immunity, and randomness.